Chronic ulcerative stomatitis. Relation to lichen planus - Bańka-Wrona, Agnieszka; Kołacińska-Strasz, Zofia; Łabęcka, Hanna; Kraińska, Teresa; Olszewska, Małgorzata (Dermatology Review/Przegląd Dermatologiczny, 2009)
Introduction. Chronic ulcerative stomatitis is a rare disease of the oral cavity which affects most commonly women aged 30-60 yrs. Clinically patients exhibit erosive or ulcerative lesions most commonly located on the tongue, buccal or gingival mucosa. Patients’ sera and direct immunofluorescence studies of the skin or mucosal lesions reveal the presence of squamous epithelium-specific antinuclear antibodies (SES-ANA). Typically the disease responds well to hydroxychloroquine. Objective. The aim of the article is to discuss the correlation between chronic ulcerative stomatitis and lichen planus. A review of current literature is also presented. Case report. We present a case of a 64-year-old female patient with chronic ulcerative stomatitis who after many years of disease duration developed skin lesions with clinical and histopathological characteristics of lichen planus. Conclusions. Current data show that chronic ulcerative stomatitis and lichen planus are separate diseases with different pathomechanisms and different therapeutic approaches.